Silica‐Bound 3‐{2‐[Poly(ethylene Glycol)]ethyl}‐Substituted 1‐Methyl‐1H‐imidazol‐3‐ium Bromide: A Recoverable Phase‐Transfer Catalyst for Smooth and Regioselective Conversion of Oxiranes to β‐Hydroxynitriles in Water. Issue 2 (18th February 2013) - Reza Kiasat, Ali; Ayashi, Neda; Fallah‐Mehrjardi, Mehdi
Abstract A series of β‐hydroxynitriles were efficiently synthesized from the regioselective ring opening of oxiranes by cyanide anion in the presence of silica‐bound 3‐{2‐[poly(ethylene glycol)]ethyl}‐substituted 1‐methyl‐1H‐imidazol‐3‐ium bromide (SiO2PEGImBr) as a novel recoverable phase‐transfer catalyst in H2O (Scheme 1 and Table 2). The workup procedure was straightforward, and the catalyst could be reused over four times with almost no loss of catalytic activity and selectivity.